Common ownership and innovation efficiency - Li, Xuelin; Liu, Tong; Taylor, Lucian A. (Journal of Financial Economics, 2023)
How does common ownership affect innovation? We study this question using project-level data on pharmaceutical startups and their venture capital (VC) investors. We find that common ownership leads VCs to hold back projects, withhold funding, and redirect innovation at lagging startups. Effects are stronger where R&D costs are larger, consistent with common owners aiming to cut duplicate costs. Effects are also stronger where technological similarity is greater and preexisting competition is lower, consistent with common owners seeking market power for their surviving projects. Overall, common VC ownership appears to generate social benefits , via improved innovation efficiency, but also social costs.